Pengaruh Pertumbuhan Aset dan Tingkat Suku Bunga Sertifikat Bank Indonesia (SBI) Terhadap Kebijakan Dividen dan Nilai Perusahaan Pada Perusahaan Manufaktur di Bursa Efek Indonesia (BEI) - Rismawati, Ni Made; Dana, I Made (E-Jurnal Manajemen; Vol 3 No 4 (2014), 2014)
The establishment of a firm aimed to obtain maximum profit, the welfare of the owner of the firm or its shareholders and maximize the firm value. In order for the purpose of the firm can be achieved with the maximum, a firm needs to consider the variables that affect the firm value. This research conducted to determine the significance of the effect of asset growth and the interest rate of Bank Indonesia Certificates ( SBI ) on dividend policy and firm value. The study was conducted at the Indonesian Stock Exchange (BEI). The sample was determined by purposive sampling method and obtained 11 companies that meet the criteria. The analysis technique used path analysis or path analysis. Based on the results of the analysis found that assets growth significant negative effect on dividend policybut has no effect on firm value, interest rate of Bank Indonesia Certificates (SBI) significant positive effect on dividend policy but significant negative effect on firm value, dividend policy significant positive effect on firm value. Keywords : firm value, assets growth, the SBI interest rate, dividend policy.